2020
DOI: 10.1136/jitc-2019-000110
|View full text |Cite
|
Sign up to set email alerts
|

Identification of tumor immune infiltration-associated lncRNAs for improving prognosis and immunotherapy response of patients with non-small cell lung cancer

Abstract: BackgroundIncreasing evidence has demonstrated the functional relevance of long non-coding RNAs (lncRNAs) to immunity regulation and the tumor microenvironment in non-small cell lung cancer (NSCLC). However, tumor immune infiltration-associated lncRNAs and their value in improving clinical outcomes and immunotherapy remain largely unexplored.MethodsWe developed a computational approach to identify an lncRNA signature (TILSig) as an indicator of immune cell infiltration in patients with NSCLC through integrativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
195
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 223 publications
(213 citation statements)
references
References 45 publications
8
195
0
Order By: Relevance
“…Traditional diagnosis methods, such as the biopsy, endoscopy, and chest X-ray and CT, were inadequate for early diagnosis, and there is the lack of specific and sensitive biomarkers for earlier detection of OSCC. Alteration in molecular profiles have been observed in various human cancers compared to corresponding normal tissues, and have been used as novel markers for cancer diagnosis and prognosis (Mehta et al, 2010;Jurgensmeier et al, 2014;Chen et al, 2018Chen et al, , 2019Sun et al, 2020). lncRNAs are recently emerging as a novel promising biomarker for cancer diagnosis and prognosis (Shi et al, 2016;Bolha et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Traditional diagnosis methods, such as the biopsy, endoscopy, and chest X-ray and CT, were inadequate for early diagnosis, and there is the lack of specific and sensitive biomarkers for earlier detection of OSCC. Alteration in molecular profiles have been observed in various human cancers compared to corresponding normal tissues, and have been used as novel markers for cancer diagnosis and prognosis (Mehta et al, 2010;Jurgensmeier et al, 2014;Chen et al, 2018Chen et al, , 2019Sun et al, 2020). lncRNAs are recently emerging as a novel promising biomarker for cancer diagnosis and prognosis (Shi et al, 2016;Bolha et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…High TMB indicates the presence of more neoantigens in the tumor microenvironment, which promote the in ammatory response and result in the alteration of transcriptomic and epigenetic signature [47]. It has been proved that gene expression signatures in the tumor microenvironment were associated with the prognosis in NSCLC [48][49][50][51]. In agreement with previous studies, the differentially expressed genes between TMB-H and TMB-L patients identi ed in this study were found to enrich in the immune-related damaged DNA binding, nuclear division, nuclear chromosome segregation, organelle ssion, single-stranded DNA binding, ribonucleoprotein complex binding and pyrimidine metabolism (Additional le 2: Figure S2) [52][53][54][55][56].…”
Section: Discussionmentioning
confidence: 99%
“…Machine learning method is a good choice to uncover underlying patterns (Stephenson et al, 2019). It has been widely employed in bioinformatics (Cao et al, 2017;Bao et al, 2019;Conover et al, 2019;Moritz et al, 2019;Stephenson et al, 2019;Zou and Ma, 2019;Sun et al, 2020). The current work aims to develop a machine learning based method to diagnose HCC within-sample REOs.…”
Section: Introductionmentioning
confidence: 99%